Enhancing Focus and Short Reaction Time in Épée Fencing: The Power of the Science Vision Training Academy System - Di Martino, Giulia; Giommoni, Stefano; Esposito, Fosco; Alessandro, Davide; Della Valle, Carlo; Iuliano, Enzo; Fiorilli, Giovanni; Calcagno, Giuseppe; di Cagno, Alessandra (Journal of functional morphology and kinesiology, 2024)
Background: This study aimed to evaluate the effects of a six-week visual training protocol, based on the Science Vision Training Academy (SVTA) method, on reaction times and executive functions in high-ranking fencers. Methods: Twenty-seven fencers, aged 17.34 ± 3.63 years, were randomly assigned to an experimental Visual Training Group (VTG = 16) and a Control Group (CG = 11). The VTG, in addition to regular fencing training, underwent SVTA training two times per week using six different visual modules, while the CG followed only their traditional fencing training. Simple and complex reaction times and movement times were assessed before and after the intervention using the Fit-Light System. Results: Both groups showed a significant improvement in all four reaction time tests: simple reaction time with and without a weapon and complex reaction time ability (motor inhibition ability) with and without a weapon (p < 0.001). No significant differences were observed between the groups. A significant Time* Group interaction was found in the short reaction time and movement time (p < 0.001). This trend suggests that, although genetically determined and difficult to significantly improve through training, short reaction time can be stimulated through SVTA protocols. Conclusions: Training in realistic conditions is always preferable to non-ecological protocols; however, the SVTA method may be beneficial to enhance simple reaction time in elite fencers.